Patient sources of diet and nutrition information after a cancer diagnosis. (2020) - Mullee, Amy; Burke, Deirdre; McSharry, Veronica; Dhuibhir, Pauline Ui; Barrett, Michelle; Roulston, Fiona; Donnelly, Yvonne; Higgins, Keira; Gallagher, Julie; Casey, Louise; Stewart, Gillian; O'Donoghue, Niamh; et al.
Abstract: Cancer patients experience many diet and nutrition-related problems, which are often under-recognised and under-treated. Research suggests few healthcare professionals discuss dietary information with cancer patients. Consequently, patients may seek information from other sources. It is unknown what these information sources are or what types of advice patients obtain and follow. The aim of this study was to determine the source and type of diet information cancer patients obtain before their first dietetic assessment and the degree to which this is followed. This was a prospective, multi-center, cross-sectional observational study. Ethical approval was obtained for each centre. Consecutive cancer inpatients and outpatients were recruited for six months at seven tertiary centers. Patients were screened for eligibility. Inclusion criteria included solid tumour, over 18 years of age, new dietetic referral and ability to sign consent. Data collection was carried out by a dietitian during initial routine dietetic assessment. Participants were asked four questions about dietary advice since cancer diagnosis. To date, 74 participants (50% female) with a median age 60 (range 23–80) have been recruited. Forty percent reported weight loss of ≥ 5%. The median time from diagnosis to initial dietetic assessment was 3 months (range 0–242). Patients who obtained advice did so from several sources (median 2 sources per patient, range 0–6) prior to dietetic referral. In rank order these were; 1) family or friend (n = 31), 2) health professional (n = 24), 3) online forums or websites (n = 16) and 4) media (n = 14). Twenty-one (28%) had received no dietary advice. The most frequent advice obtained related to avoidance of certain foods; particularly dairy, meat and sugar. Fruit, vegetables, protein, juices and wholegrain were advised. Fifty-one percent followed the advice fully and 4% partially. Seven expressed disappointment at not having a dietetics referral earlier and identified the need for the hospital "to introduce good information early". In conclusion, the majority of dietary and nutritional advice prior to dietetic referral came from friends, family, media and online forums and websites. Most advice related to the avoidance and/or promotion of particular foods. Cancer patients want dietary advice from dietitians at diagnosis to prevent unnecessary avoidance of certain foods and to reduce the risk of unintentional weight loss.